Oleic acid/oleylamine ligand pair: a versatile combination in the synthesis of colloidal nanoparticles - Mourdikoudis, Stefanos; Menelaou, Melita; Fiuza-Maneiro, Nadesh; Zheng, Guangchao; Wei, Shuangying; Pérez-Juste, Jorge; Polavarapu, Lakshminarayana; Sofer, Zdeněk (Nanoscale horizons, 2022)
A variety of colloidal chemical approaches has been developed in the last few decades for the controlled synthesis of nanostructured materials in either water or organic solvents. Besides the precursors, the solvents, reducing agents, and the choice of surfactants are crucial for tuning the composition, morphology and other properties of the resulting nanoparticles. The ligands employed include thiols, amines, carboxylic acids, phosphines and phosphine oxides. Generally, adding a single ligand to the reaction mixture is not always adequate to yield the desired features. In this review, we discuss in detail the role of the oleic acid/oleylamine ligand pair in the chemical synthesis of nanoparticles. The combined use of these ligands belonging to two different categories of molecules aims to control the size and shape of nanoparticles and prevent their aggregation, not only during their synthesis but also after their dispersion in a carrier solvent. We show how the different binding strengths of these two molecules and their distinct binding modes on specific facets affect the reaction kinetics toward the production of nanostructures with tailored characteristics. Additional functions, such as the reducing function, are also noted, especially for oleylamine. Sometimes, the carboxylic acid will react with the alkylamine to form an acid-base complex, which may serve as a binary capping agent and reductant; however, its reducing capacity may range from lower to much lower than that of oleylamine. The types of nanoparticles synthesized in the simultaneous presence of oleic acid and oleylamine and discussed herein include metal oxides, metal chalcogenides, metals, bimetallic structures, perovskites, upconversion particles and rare earth-based materials. Diverse morphologies, ranging from spherical nanoparticles to anisotropic, core-shell and hetero-structured configurations are presented. Finally, the relation between tuning the resulting surface and volume nanoparticle properties and the relevant applications is highlighted.
Keywords: Ligands; oxidy; aminy; Oleic Acid; ligandy; Solvents; kyselina olejová; rozpouštědla; Nanoparticles; Amines; Oxides; nanočástice